Rol de los medios de comunicación públicos en la gestión del presidente Lenín Moreno durante la pandemia por el COVID19, año 2020. - Barreno Mantilla, Martín Javier (2022)
In the first months of 2020, the entire world lived the beginning of the coronavirus pandemic, therefore, the media in Ecuador were the main tool of the government to keep the population informed about new infections, mobility restrictions, deceased by contagion with the disease, biosecurity measures, also, the YouTube platforms of the media were important since videos were published in them showing the different economic, safety and health measures that the government took. government of president Lenin Moreno. The application of content analysis and documentary review in the messages issued by the platforms of the public media allows us to know the veracity with which their contents are elaborated, it also helps us to identify if the communicators made use of the Code of journalistic ethics so that their messages generate a positive point of view in the population. In the matrices that were analyzed, it can be seen that in the public media, President Moreno's management was continuously disseminated through the YouTube platform through: national channels, informative notes, interviews, and official communiqués